Viroids and Retrozymes: Plant Circular RNAs Capable of Autonomous Replication - Alexander A. Lezzhov; Anastasia K. Atabekova; Denis A. Chergintsev; Ekaterina A. Lazareva; Andrey G. Solovyev; Sergey Y. Morozov (Plants)
Among the long non-coding RNAs that are currently recognized as important regulatory molecules influencing a plethora of processes in eukaryotic cells, circular RNAs (circRNAs) represent a distinct class of RNAs that are predominantly produced by back-splicing of pre-mRNA. The most studied regulatory mechanisms involving circRNAs are acting as miRNA sponges, forming R-loops with genomic DNA, and encoding functional proteins. In addition to circRNAs generated by back-splicing, two types of circRNAs capable of autonomous RNA-RNA replication and systemic transport have been described in plants: viroids, which are infectious RNAs that cause a number of plant diseases, and retrozymes, which are transcripts of retrotransposon genomic loci that are capable of circularization due to ribozymes. Based on a number of common features, viroids and retrozymes are considered to be evolutionarily related. Here, we provide an overview of the biogenesis mechanisms and regulatory functions of non-replicating circRNAs produced by back-splicing and further discuss in detail the currently available data on viroids and retrozymes, focusing on their structural features, replication mechanisms, interaction with cellular components, and transport in plants. In addition, biotechnological approaches involving replication-capable plant circRNAs are discussed, as well as their potential applications in research and agriculture.